Transfection of microRNA Mimics Should Be Used with Caution - Jin, Hyun Yong; Gonzalez-Martin, Alicia; Miletic, Ana V.; Lai, Maoyi; Knight, Sarah; Sabouri-Ghomi, Mohsen; Head, Steven R.; Macauley, Matthew S.; Rickert, Robert C.; Xiao, Changchun (Frontiers in Genetics, 2015)
Transient transfection of chemically synthesized microRNA (miRNA) mimics is being used extensively to study the functions and mechanisms of endogenous miRNAs. However, it remains unclear whether transfected miRNAs behave similarly to endogenous miRNAs. Here we show that transient transfection of miRNA mimics into HeLa cells by a commonly used method led to the accumulation of high molecular weight RNA species and a two to three hundred fold increase in mature miRNA levels. In contrast, expression of the same miRNAs through lentiviral infection or plasmid transfection of HeLa cells, transgenic expression in primary lymphocytes, and endogenous overexpression in lymphoma and leukemia cell lines did not lead to the appearance of high molecular weight RNA species. The increase of mature miRNA levels in these cells was below ten fold, which was sufficient to suppress target gene expression and to drive lymphoma development in mice. Moreover, transient transfection of miRNA mimics at high concentrations caused non-specific alterations in gene expression, while at low concentrations achieved expression levels comparable to other methods but failed to efficiently suppress target gene expression. Small RNA deep sequencing analysis revealed that the guide strands of miRNA mimics were frequently mutated, while unnatural passenger strands of some miRNA mimics accumulated to high levels. The high molecular weight RNA species were a heterogeneous mixture of several classes of RNA species generated by concatemerization, 5’- and 3’-end tailing of miRNA mimics. We speculate that the supraphysiological levels of mature miRNAs and these artifactual RNA species led to non-specific changes in gene expression. Our results have important implications for the design and interpretation of experiments primarily employing transient transfection of miRNA mimics.